Acute urinary retention in children - Schmidt, Ana Marija; Hirsch, Karin; Schroth, Michael; Stehr, Maximilian; Schäfer, Frank-Mattias (Journal of Pediatric Urology, 2020)
Background: Acute urinary retention is a common emergency in adult patients, foremost in older men. In childhood urinary retention is a rare entity with only sparse literature on the etiology. Objective: To assess the etiology and treatment of acute urinary retention in the pediatric population and assess age and sex distribution. Study design: A retrospective analysis of all patients admitted to our emergency department with acute urinary retention between 2005 and 2019 was performed. Exclusion criteria were newborns (because of physiologic postnatal oliguria) and postoperative urinary retention during the same hospital stay. Results: 113 children with acute urinary retention (ICD: R33) meeting the above criteria were identified. 16 Patients were excluded because of incomplete medical charts. 97 children were included into the study (age 0.5–18.3 years, mean age 5.3 years). 89 patients had one episode, 8 patients two episodes. A peak around the third year of age was observed. Sex ratio showed a 2:1 male to female distribution. Most common etiology was balanoposthitis (15.5%) and acute constipation/fecal impaction (15.5%). Traumatic urinary retention was found in 11.4% of the cases. Urinary tract infection were found 7.2%. No underlying reason could be found in 12.4% (idiopathic urinary retention). Other causes included febrile non-urinary infection (8.2%), subvesical obstruction (4.1%), vulvovaginitis (3.1%) and urethritis (2.1%). In 50% of the cases of urinary retention under 1 year of age (2 out of 4) an underlying tumor (rhabdomyosarcoma, sacral teratoma) was identified. Discussion: Age and sex distribution were similar to previously published series; however, this study shows a marked difference concerning the etiology: e. g. we identified a significantly higher proportion of functional disorders as a reason for acute urinary retention in childhood. It is hypothesized that this is partly because previously published studies originate from areas (USA, Israel, Iran) with different socio-demographic and cultural background. Conclusion: AUR in children is a rare condition with very heterogeneous causes. Although the majority of cases exhibit mild underlying conditions, serious reasons, such as malignant diseases especially in the first year of life, must be excluded. AUR relief without catheterization is a child-friendly approach in cases of mild inflammatory or functional disorders and can help to minimize traumatization. [Table presented]
CRIS-Team Scopus Importer:2020-12-18
Keywords: Acute urinary retention; Balanoposthitis; Fecal impaction; Functional disorders; Urinary tract infection